Pengaruh Kualitas E-Ticketing, Harga Dan Attraction Terhadap Kepuasan Konsumen Di Dunia Fantasi Jakarta Utara - Wati, Suci Mey Setia; Iskandar, Donant Alananto (STREAMING, 2025)
This research aims to determine whether the quality of e-ticketing, price and attraction affect consumer satisfaction at Dunia Fantasi, North Jakarta. An associative quantitative approach was used, which involved analyzing the relationship between two variables through the distribution of questionnaires to 115 respondents who were consumers who had purchased tickets to Dunia Fantasi North Jakarta. This research includes validity testing, reliability testing, classical assumption testing, main testing and hypothesis testing. The sampling method used was non-probability using a purposive sampling method. Researchers processed the data using SPSS 22. The survey distributed by the author was a questionnaire using Google from to 115 respondents online. Based on the hypothesis in the t test, overall e-ticketing quality, price and attraction together have a significant influence on consumer satisfaction.